Congenital cystic mesoblastic nephroma - Ganick, Dorothy J.; Gilbert, Enid F.; Bruce Beckwith, J.; Kiviat, Nancy (Human pathology, 1981)
A case of cystic mesoblastic nephroma occurring in a five month old infant is presented. This unusual case provides additional information regarding the spectrum of differentiation of both solid and cystic kidney tumors in the developing embryo. Our concept of the morphogenesis of congenital renal neoplasms is presented.